Integrating Realistic Mathematics Education and Islamic Values: A Hypothetical Learning Trajectory for Teaching Cuboid Geometry - Yulia Yulia; Rivdya Eliza; Edwin Musdi; Martin Kustati; Juli Afriadi; Miftahul Khairi Rahmadhani (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2026)
Integrating Islamic contexts into mathematics learning has recently gained increasing scholarly attention. This study aims to develop and test a Hypothetical Learning Trajectory (HLT) for learning cuboid geometry through realistic contexts embedded with Islamic values. Employing a design research approach, the study followed three key stages: (1) preparing for the experiment, (2) conducting the experimental design, and (3) conducting retrospective analysis. The HLT was implemented with Grade VIII students from three state-run Madrasah Tsanawiyah in different provinces of Indonesia (Padang, Malang, and Bandung) to capture contextual diversity and ensure the transferability of the findings. Data were collected through analysis questionnaires, students’ written work, video transcripts, and observation sheets, then analyzed using thematic coding and descriptive analysis aligned with the RME framework. The findings indicate that integrating Islamic values within realistic contexts supported students in constructing geometric concepts meaningfully while internalizing the moral and cultural dimensions of learning. Empirically, the study is limited by its small-scale implementation and focus on a single mathematical topic; Therefore, future research should expand to broader mathematical domains and explore longitudinal impacts to strengthen evidence-based recommendations for culturally responsive mathematics education.